2020
DOI: 10.1177/1535759720935825
|View full text |Cite
|
Sign up to set email alerts
|

Promoting CRISPRa for Targeted Treatment of Epilepsy

Abstract: [Box: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Another primary concern is passing through the blood-brain barrier (BBB) system, as this physiological barrier holds the cerebral microenvironment very tightly and isolates it completely from other segments of the human body to protect this intricate neural network system. Therefore, a well-targeted approach is required to access the BBB without disrupting its integrity and biological functioning [172]. Many approaches, such as micro dialysis and brain perfusion studies, have not performed well, though nanoparticle-based targeted delivery has shown some positive results [173][174][175].…”
Section: Challenges Associated With the Application Of Crispr In Neur...mentioning
confidence: 99%
“…Another primary concern is passing through the blood-brain barrier (BBB) system, as this physiological barrier holds the cerebral microenvironment very tightly and isolates it completely from other segments of the human body to protect this intricate neural network system. Therefore, a well-targeted approach is required to access the BBB without disrupting its integrity and biological functioning [172]. Many approaches, such as micro dialysis and brain perfusion studies, have not performed well, though nanoparticle-based targeted delivery has shown some positive results [173][174][175].…”
Section: Challenges Associated With the Application Of Crispr In Neur...mentioning
confidence: 99%
“…In a model of temporal lobe epilepsy, findings have demonstrated a decrease in spontaneous generalized tonic–clonic seizures as well as transcriptome changes related to chronic epilepsy. This work demonstrates that CRISPR is also a viable epilepsy therapy strategy [ 40 ]. Additionally, cellular therapy is one type of regenerative medicine that uses stem cells to repair a site of the body that has been diseased or damaged.…”
Section: The Rise Of Seizures In Brain Areasmentioning
confidence: 99%